Pengaruh Kepemimpinan Kepala Desa Terhadap Partisipasi Masyarakat Dalam Pembangunan Di Desa Citengah Kec. Sumedang Selatan Kabupaten Sumedang - Setiadi, Ade; Mulyaningsih, Mulyaningsih; Ulumudin, Aceng (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2025)
This study aims to analyze the role of inclusive and participatory leadership in increasing community engagement in village development. Using a qualitative descriptive approach, this research examines the leadership style of village heads in Citengah Village and its impact on public participation. Data collection was conducted through interviews, observations, and document analysis, which were then processed using qualitative data reduction, presentation, and verification techniques. The findings indicate that community participation in decision-making and development implementation remains low due to ineffective government communication, limited public awareness, and bureaucratic constraints. The passive role of the community has resulted in weak ownership of development programs, reducing their effectiveness and sustainability. The research highlights that village heads who apply adaptive and participatory leadership can create a more conducive environment for active community involvement. Open dialogue, collaboration with the Village Consultative Body (BPD), and inclusive policy-making processes enhance transparency and accountability in village governance. Additionally, technology-based communication strategies, such as social media platforms and digital community forums, improve public access to information and allow broader participation. Strengthening digital literacy and community education on development policies also plays a crucial role in fostering awareness and engagement. This study concludes that enhancing the leadership capacity of village heads in communication, transparency, and digital integration is essential for building more democratic and participatory governance. Implementing these strategies is expected to lead to more effective, inclusive, and sustainable village development that aligns with the needs and aspirations of the community.